Challenges with the control of non-communicable disease burden - Borodo, M. M. (Nigerian Journal of Basic and Clinical Sciences, 2026)
While the manifestations of noncommunicable disease (NCD) is bread and butter in the developed world, the rising profile of this group of health problems is yet to reach its peak in the less developed parts of the world as its predicted global epidemic in the next two decades promises to unleash most of its venom in that region with expected devastating consequences in morbidity and mortality figures of the population, unless appropriate strategies are put in place.